A case of Prader-Willi syndrome with a deletion including MAGEL2 , NDN , and MKRN3 , but excluding SNRPN and SNORD116 - Bücking, Jannis; An, Yu; Bi, Weimin; Hinderhofer, Katrin; Theiß, Susanne; Slavotinek, Anne; Schaaf, Christian P. (American journal of medical genetics, 2025)
Prader-Willi syndrome (PWS) is a neurodevelopmental disorder typically caused by large deletions or imprinting defects on chromosome 15q11.2, encompassing multiple genes. While the contribution of individual genes to the PWS phenotype remains unclear, previous studies suggested that isolated deletions of MAGEL2, NDN, and MKRN3, excluding the SNRPN/SNORD116 locus, were insufficient to cause PWS. Here, we present a case report of a patient with an isolated deletion of MAGEL2, NDN, and MKRN3 who exhibits the full PWS phenotype, including neonatal hypotonia, developmental delay, hyperphagia, obesity, and behavioral issues. We explore the potential mechanisms underlying this case and investigate the potential contribution of the deleted genes to the observed phenotype. This case challenges previous findings and highlights the complexity of genotype-phenotype correlations in PWS. We compare the clinical data of our patient with previous reports and discuss the discrepancy with earlier findings. Our findings underscore the need for further research to fully elucidate the roles of individual genes within the PWS locus and the mechanisms underlying the phenotypic spectrum of this complex disorder.
Veröffentlicht: 15 April 2025
Gesehen am 30.01.2026